Health effects of rubber wood dust exposure among workers in a furniture factory - Yusof, Muhammad Zubir; Hod, Rozita; Noor Aizuddin, Azimatun; Samsuddin, Niza (2011)
Introduction: Potential health impacts resulting from wood dust exposure among workers in the furniture factories have been reported in many studies. However, most of the studies focused on pine, beech, teak, oak and red western cedar. There is still lack of studies pertaining to the health effects due to exposure to rubber wood (Hevea brasiliensis) dust.